Development culture in small energy-rich Islamic countries; A case study of Brunei Darussalam - Aziz, M (Cranfield University, 2010)
The starting point for this study is the sense that the Brunei economy, whilst not stagnating, has been performing less well than other economies in the region and beyond. Of course, there is a need to compare like with like, and in this regard Brunei should be compared with other states possessing the same characteristics, ie, small, oil-dependent, Islamic, monarchies; and such a comparison suggests that Brunei is no Dubai. Accordingly, the study hypothesizes that Brunei is suffering from a resource ‘curse’; that the possession of oil and gas resources and ‘easy’ money have repressed the people’s work ethic and blunted the drive towards innovational and creative endeavour. The study focus is on Brunei, but a comparative evaluation is undertaken of three small, energy-rich, Islamic Gulf states: Bahrain, Oman and Qatar. By using proxies of economic performance, the research attempts to uncover the existence, or otherwise, of a development culture. Findings indicate that all four of the oil- dependent states suffer, to a greater or lesser extent, from a resource curse. However, the Gulf States have proved more successful than Brunei in diversifying their economies and overcoming the cultural slothfulness associated with a dependence on energy resources. This study identifies the benefits from the Gulf States’ experience of fusing capitalism with Islam, and, thus a principal finding of the study is that Brunei should emulate some of the major features of this development model. Explicitly, Brunei should pursue the growth opportunities of capitalism, but without sacrificing its own unique cultural identity.